Capacity of a multibeam, multisatellite CDMA mobile radio network with interference-mitigating receivers. - De Gaudenzi, R. (IEEE Journal on selected areas in communications)
More and more interference-mitigating algorithms are being investigated in an attempt to increase the capacity of code-division multiple-access radio networks. At the moment, the main question about interference-resilient receivers is: do they really bring forth the capacity increase they promise on theoretical grounds? The aim of this study is to give a preliminary answer to such a question, through the capacity analysis of the forward link of a multisatellite, multibeam, radio communication network. Specifically, starting from simplified yet realistic assumptions on the beam layout, the antenna footprint shape, and the coding/multiplexing/modulation and power control strategies, it is shown that the blind, adaptive, interference-mitigation receiver, selected as an appealing representative of the lot, can indeed boost the system quality of service in terms of outage probability. The results are derived after a mix of theoretical analysis (as far as the detector performance evaluation is concerned) and simulation (to examine a number of different random system configurations) to circumvent the inherent complexity of the issue